Vocational Psychology: Expanding the Vision and Enhancing the Impact ψ. (February 2019) - Blustein, David L.; Ali, Saba Rasheed; Flores, Lisa Y.
In this contribution, we provide a critical analysis of the current status of vocational psychology and present an expansive vision for the future. We begin with an overview of the importance of vocational psychology in the history of The Counseling Psychologist, followed by a critical review of contemporary theory, research, practice, and training. We aim to expand the traditional purview of career choice and development and broaden the impact of the field to meet the needs of all who work and who want to work. We propose a new mission for vocational psychology characterized by innovative theoretical advancements, renewed interdisciplinary and international collaborations, and the inclusion of macrolevel factors in research, practice, and policy. Lastly, we conclude with a vision of vocational psychology in 20 years, which optimally will be reflected in a broadened scope of mission, integrative theoretical frameworks, and an expanded training and policy agenda.